"New normal" at work in a post-COVID world: work–life balance and labor markets. Issue 1 (20th January 2022) - Vyas, Lina
Abstract: The coronavirus pandemic has interrupted labor markets, triggering massive and instant series of experimentations with flexible work arrangements, and new relationships to centralized working environments. These approaches have laid the basis for the "new normal, " likely extending into the organization of work in the post-pandemic era. These new arrangements, especially flexible work arrangements, have challenged traditional relationships with employees and employers, work time and working hours, the work–life balance (WLB), and the relationship of individuals to work. This paper investigates how labor markets have been interrupted due to the pandemic, focusing especially on manual (blue-collar) and nonmanual (white-collar) work and the future of the WLB, along with exploring the projected deviations that are driving a foreseeable future policy revolution in work and employment. This paper argues that although hybrid and remote working would be more popular in the post-pandemic for nonmanual work, it will not be "one size fits all" solution. Traditional work practices will remain, and offices will not completely disappear. Manual labor will continue current work practices with increased demands. Employers' attention to employees' WLB in the new normal will target employees' motivation and achieving better WLB. These trends for the labor market and WLB are classified into three categories—those that are predicated on changes that were already underway but were accelerated with arrival of the pandemic ("acceleration"); those that represent normalization of what were once considered avant-garde ways of work ("normalization"); and those that represent modification or alteration of pre-pandemic set-up ("remodelling").